Odpowiedzi

2010-03-22T17:03:01+01:00
(x+5)²-(x-3)²=x+1
x² + 10x + 25 - (x² - 6x + 9) = x + 1
x² + 10x + 25 - x² + 6x - 9 - x = 1
15x = 1 + 9 - 25
15x = - 15
x = - 15/15 = - 1
x = - 1

(x-2)²-(x-5)(x+5)>-4(x+5)
x² - 4x + 4 - (x² - 25) > -4x - 20
x² - 4x + 4 - x² + 25 > -4x - 20
- 4x + 4x > - 20 - 25 - 4
0 > - 49
2010-03-22T17:08:22+01:00
(x+5)do kwadr - (x-3) do kwadr = x+1
x kwadr +10x + 25 -(x kwadr - 6x +9) = x+1
x kwadr +10x + 25 -x kwadr +6x -9=x+1
16x+16=x+1
15x=-15
x=-1

(x-2) do kwadr - (x-5)(x+5) ` -4(x+5)
x kwadr -4x -(x kwadr -25)` -4x-20
x kwadr -4x - x kwadr +25` -4x-20